Taxonomical update of the genus Drypetes (Malpighiales: Putranjivaceae) in Cuba - Leyva, Luis Manuel; García-Beltrán, José Angel (Phytotaxa, 2024)
Drypetes is a pantropical genus of 220 species of dioecious trees and shrubs, where around 20 of them are found in the Americas, with a hotspot in the West Indies. In Cuba, the number of taxa and its identities have changed throughout the years and the infraspecific classification has never being taken into consideration. In this sense, the taxa delimitation and nomenclature of Drypetes in Cuba is reviewed. The infraspecific classification of D. alba is recognized, and a new status is presented: D. alba subsp. latifolia. The lectotypes for four names are designated: D. glauca, D. glomerata var. olivacea, D. mucronata and Schaefferia lateriflora. For all Cuban taxa, the diagnostic features and nomenclatural information are presented, as well as the updated geographical distribution. The presence of Drypetes glauca in Cuba is rejected. Thus, this genus in Cuba is represented with two species and one subspecies. Also, an identification key for the genus in the West Indies is given.